2020
DOI: 10.1016/j.mechatronics.2019.102318
|View full text |Cite
|
Sign up to set email alerts
|

Varying mechanical compliance benefits energy efficiency of a knee joint actuator

Abstract: In the field of wearable robots, actuator efficiency and user safety are frequently addressed by intentionally adding compliance to the actuation unit. However, the implications compliance has on the actuator's overall performance in different conditions and activities are not fully understood, largely due to single task-focused experimental evaluations of these devices. To overcome this, our paper analyzes the effects that changing mechanical compliance has on the actuator's overall performance in different i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The second parameter investigated in this study is the actuator's stiffness level. The influence of this parameter on the actuator's performance has been already shown in several test-bench experiments [37,40]. In [37] it was shown that no single stiffness level of the ankle actuator used in the MAPO could be defined as optimal based on the actuator's torque tracking performance, due to the dependence of the benefits of a specific actuator's stiffness level on both the assistive torque reference and the user's ankle kinematics.…”
Section: Introductionmentioning
confidence: 93%
“…The second parameter investigated in this study is the actuator's stiffness level. The influence of this parameter on the actuator's performance has been already shown in several test-bench experiments [37,40]. In [37] it was shown that no single stiffness level of the ankle actuator used in the MAPO could be defined as optimal based on the actuator's torque tracking performance, due to the dependence of the benefits of a specific actuator's stiffness level on both the assistive torque reference and the user's ankle kinematics.…”
Section: Introductionmentioning
confidence: 93%
“…1). The actuator's defining features are a simple rotational joint (viable choice for knee orthosis [25], [32]), anthropomorphic shape designed to minimise potential negative effects of its 2.2 kg mass [33], and a spring in series with an EC motor to deliver torque in the sagittal plane (see [34], [35] for detailed actuator specifications and performance).…”
Section: A Knee Joint Orthosismentioning
confidence: 99%
“…The motor is controlled at a low level using a controller provided by the manufacturer. This cascaded controller allows reliable delivery of any desired torque within the actuator's hardware/software limitations without measuring the torque [35].…”
Section: B Control Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…In Li et al (2019), a compliant crank-slider mechanism can be constructed by adding constant-stiffness springs at its joints. In Baček et al (2020), the authors analyzed the effects that changing mechanical compliance has on the actuator's overall performance in different ideal conditions in an experimental test setup.…”
Section: Introductionmentioning
confidence: 99%